The Practice of Phra Thepphawanavikrom (Boonma Punyapirato) - Phrakhru Phisitchayanukul; Parisuttamo , Phramahakhawin (Academic MCU Buriram Journal, 2023)
This thesis article is a study of the merit making of Phra Thepbhavanavikrom (Boonma Punyaphirato) with two objectives: 1) to study the merit making according to the Buddhist way; 2) to propose a guideline for merit making of Phra Thepbhavanavikrom (Boonma Punyaphirato) by storing data in data aggregation and from an interview with the people of Ban Na Udom, Chaiyaphum Phithak Temple, Kut Chum Saeng Subdistrict, Nong Bua Daeng District, Chaiyaphum Province, 10 people, 5 experts/person, villagers and close-up people, 5 monks/person, using a specific method according to the issue to be researched, 10 people, with a study guideline for data collection. The research results found that: The study found that merit making according to the Buddhist way. There is a specific form of Amisadanam (Material Donation) practice. It is giving objects, Dhammadanam (Dhamma offerings); giving knowledge, giving wisdom, Apayadanam; forgiveness without holding onto anger. The three ways of eating are the ways that are explained in Buddhism that shows how to follow the example to gain access to alms. Therefore, the meritorious practice of Phra Thepbhavanavikrom (Bunma Punyaphirato) in terms of being in the form of a Buddhist that requires the basic practice of knowing the sacrifice of objects by practicing according to the Dhamma, Buddhist teaching through the promotion by granting scholarships to monks and novices and also promote the place to education by constructing places like the Chaiyaphum Buddhist College. Phrathepbhavanavikrom has made merit by creating a society that only gives in a way that follows the teachings of the Phrathepbhavanavikrom with the sacrifice of merit.